Locating Religions Contact, Diversity, and Translocality - Glei, Reinhold; Jaspert, Nikolas (Dynamics in the History of Religions, 2016)
This collection of articles applies concepts developed in the wake of the so-called "spatial turn" to the field of religious studies.; Readership: All interested in processes of interaction between societies and inidividuals of different creeds and cultures: historians, anthropologists, theologians.